Isolation and Analysis of Chemical Components of Garlic (Allium sativum L.) Tuber Essential Oil As Well As Antibacterial and Antioxidant Activity Tests - Perangin-angin, Sabarmin; Pratama, Dimas A (Talenta Publisher, 2022)
The essential oil from garlic tubers (Allium sativum L) was isolated by hydrodistillation method using the Stahl apparatus. Garlic tubers were distilled for 4 to 5 hours to produce as much oil as 0.05% (w/ w). The chemical components of essential oil of garlic tubers were analyzed using GC-MS spectroscopy. The GC-MS results showed that there were 11 components with 5 main components, namely diallyl disulfide (44.98%), 1,3-diallyl tri sulfane (13.63%), allyl sulfide (13.06%), methyl allyl disulfide (11.87%), and methyl allyl trisulfide (4.84%). The antibacterial activity of essential oil of garlic tubers with diffusion method to use concentration variation of 5%, 10%, and 15% have strong antibacterial activity against Gram-positive bacteria like Staphylococcus aureus and have a medium to strong antibacterial activity against Gram-negative bacteria like Escherichia coli. The antioxidant activity of the essential oil of garlic tubers with DPPH (2,2-diphenyl-1-picrylhydrazil) showed an IC50 value was 22.863 mg/L and a very strong antioxidant group.